Folklore of the Karaites in Lithuania: the Yehuda Bezekowicz Manuscript from Troki, 1873 - Muchowski, Piotr (Karaite Archives, 2014)
The Heb 8°3652 manuscript from the National Library of Israel is among a collection of rare manuscripts from 19th-century Lithuania containing unofficial Karaite literature. These manuscripts, including the Abkowicz 3 and JSul.I.05 manuscripts, contain a vast collection of texts relating to the practical cabbala. Some of them are typical of divination and magic literature, and many resemble parallel texts from the Cairo Geniza in their form and contents. Their presence in Karaite manuscripts is exceptional for theological reasons. The Karaite translations of these texts were presented by professor Ananiasz Zajączkowski in the inter-war period as representative evidence of Karaite folklore and folk literature. This article includes an introductory presentation of the Heb 8.3652 manuscript.